(untitled) (Universal International Scientific Journal, 2026)
In this study, the properties of cement obtained by adding technogenic waste from filter systems of asphalt plants of Surkhandarya region as an additive to the composition of Portland cement of the SEM II/A-I 32.5N brand were studied. Filter waste was added in an amount of 3.5–10% relative to clinker. Test samples were prepared in accordance with the requirements of GOST 197-(1,2,3)-2020 and their compressive strength was measured at 2, 7 and 28 days. The results showed that the optimal addition amount of 5–7.5% increased the cement strength at 28 days. Due to the high dispersion of waste, a denser C–S–H gel was formed, and the porosity of concrete decreased. This approach allows reducing clinker consumption, increasing energy efficiency and reducing the environmental load. The resulting cement is recommended for monolithic and prefabricated reinforced concrete structures, road surfaces, and water structures.